2004
DOI: 10.1111/j.1572-0241.2004.04149.x
|View full text |Cite
|
Sign up to set email alerts
|

Critical Factors Affecting Quality of Life of Adult Patients With Anorectal Malformations or Hirschsprung's Disease

Abstract: The quality of life of patients with ARM or Hirschsprung's disease was found to be comparable. Compared to healthy people, both patient groups encountered "overall" physical health problems, but only patients with ARM reported additional pain and limitations in role functioning due to physical problems. It appeared that psychosocial functioning had the most important effect on the quality of life of patients with ARM or Hirschsprung's disease, while fecal incontinence and constipation had almost no effect on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
65
1
4

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(81 citation statements)
references
References 27 publications
11
65
1
4
Order By: Relevance
“…Another recently published study showed that patients with HD encountered more "overall" physical health problems compared with healthy subjects, but HD patients did not show additional pain or limitations in functioning due to physical problems [66]. Psychosocial functioning had the most important effect on the quality of life of patients with HD, whereas fecal incontinence and constipation had almost no effect on their quality of life.…”
Section: Prognosis After Surgerymentioning
confidence: 92%
“…Another recently published study showed that patients with HD encountered more "overall" physical health problems compared with healthy subjects, but HD patients did not show additional pain or limitations in functioning due to physical problems [66]. Psychosocial functioning had the most important effect on the quality of life of patients with HD, whereas fecal incontinence and constipation had almost no effect on their quality of life.…”
Section: Prognosis After Surgerymentioning
confidence: 92%
“…The incidence is relatively high and can require extensive surgery to provide a tolerable quality of life. Even with surgical intervention the outlook for those with more serious defects is poor and for those who respond well to surgery there is often a long-term follow up required, in addition to psychological damage (Bai et al, 2000, Hartman et al, 2004. Our studies provide new insights into the molecular bases of ARMs, and suggest a robust model system for future analysis of the genetic and teratogenic contributors to ARMs.…”
Section: The Zebrafish As a Model For Armsmentioning
confidence: 99%
“…[1][2][3][4][5][6] It has been shown in several studies that there is no statistically significant difference in the functional outcome with respect to bowel function between the various pull through surgeries. [7][8][9][10][11] As with many surgery, for HD also has some long and short term complications. Faecal incontinence and constipation remains major postoperative complication that impede social and psychological developmental in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Additional modification has involved the creation of the anastomosis with the use of mechanical stapling devices. 11 An additional modification has centred around eliminating the proximal rectal pouch "SPUR" in the aganglionic rectum, which can trap large accumulation of stool. Martin and Altemeir and Martin and Caudill described careful clamp placement to entirely eliminate the rectal pouch.…”
Section: Introductionmentioning
confidence: 99%